EVALUATING THE EFFECTIVENESS OF PROPHYLACTIC REPLACEMENT THERAPY IN CHILDREN WITH HEMOPHILIC ARTHROPATHY IN DYNAMICS ON MAGNETIC RESONANCE IMAGING - I. S. Remzantseva; V. D. Zavadovskaya; L. M. Ogorodova; Z. A. Maevskaya; O. Yu. Kilina; A. N. Kailina (Union of pediatricians of Russia, 2015)
Modifications in treatment guidelines of hemophilic arthropathy changed the role of diagnostic X-ray imaging methods. Diagnostic methods are used both for determination of the degree of joint destruction and long-term evaluation of the joint conditions and therapy adequacy and effectiveness. Aim. Magnetic resonance imaging (MRI) dynamics for joint condition assessment in children with hemophilic arthropathy receiving prophylactic factor replacement therapy concentrated rolling VIII. Materials and methods. We studied 13 boys aged 5 to 14 years (mean age 8.9 years) with hemophilia type A severe form of the disease (factor VIII deficiency <1%) at the baseline. The average age of appearance of hemarthrosis is 2.1 years (from 1.8 to 2.9 years). The frequency of bleeding into the joints of patients older than 1 year was 2-3 times per year. Magnetic resonance imaging (ToshibaExcelArtVantage, 1,5 T) was performed in 13 patients, 35 joints were examined, 57 studies were executed. Control study of joints was conducted in 1, 2 or 3 years depending on the frequency of hemarthrosis during the year and the severity of joint damage primarily identified. Results. The results included both the improvement along with the stabilization of intra-state structures and the negative dynamic shifts. MRI showed that the reduction of bleeding in the joints on the background of hemostatic replacement therapy led to subsiding inflammation in the joints and significant decrease in the amount of intra-articular effusion (n = 11; p = 0.03), decrease in the number of joints with symptoms of bone marrow edema (n = 8), the absence of observations with negative changes in the form of increasing the thickness of the synovial membrane. Negative dynamics of joint condition presented as increasing of the depth and length of erosive process (n = 5; 22.7%), degenerative changes in ligaments and menisci (n = 2; 9%) under the condition of regular administration of clotting factors was associated with the development of the inhibitory form of the disease which was confirmed by laboratory data. Conclusions. Magnetic resonance imaging evaluates the effectiveness of replacement therapy in children with hemophilia.